The Coaching and Management of a Successful Organisation - Gheorghina Liliana Bir̂ladeanu (Agora International Journal of Economical Sciences (AIJES), 2022)
Exercising coaching within organisations creates efficient teams, giving them sense and direction regarding actions, with an increased and consequent focus on the employees` motivational approach and also on the ability to delegate effectively. This way, a healthy environment is cultivated, with autonomous, self-taught working teams, which activate conscientiously aspects that lead to building a successful organisation. "No one can whistle a symphony, it takes a whole orchestra to play it." (H.E. Luccock)
Keywords: 330